Leveraging on Active Site Similarities; Identification of Potential Inhibitors of Zinc-Finger and UFSP domain Protein (ZUFSP) - Ajadi, Mary B.; Soremekun, Opeyemi S.; Adewumi, Adeniyi T.; Kumalo, Hezekiel M.; Soliman, Mahmoud E.S. (Current Pharmaceutical Biotechnology, 2021)
Background: ZUFSP (Zinc-finger and UFSP domain protein) is a novel representative member of the recently characterized seventh class of deubiquitinating enzymes (DUBs). Due to the roles DUBs play in genetic instability, they have become a major drug target in cancer and neurodegenerative diseases. ZUFSP, being a DUB enzyme has also been implicated in genetic stability. However, no lead compound has been developed to target ZUFSP. Objective/Methods: Therefore, in this study, we used a combined drug repurposing, virtual screening and per-Residue Energy Decomposition (PRED) to identify ZUFSP inhibitors with therapeutic potential. 3-bromo-6-[4-hydroxy-1-3(3-phenylbutanoyl)piperidin-4-yl]methyl-4H,5H,6H,7H-thieno[2,3- C]pyridine-7-one (BHPTP) which is an inhibitor of USP7 was repurposed to target ZUFSP. The rationale behind this is based on the similarity of the active between USP7 and ZUFSP. Results: PRED of the binding between BHPTP and ZUFSP revealed Cys223, Arg408, Met410, Asn460, and Tyr465 as the crucial residues responsible for this interaction. The pharmacophoric moieties of BHPTP responsible for this binding along with other physiochemical properties were used as a filter to retrieve potential ligands. 799 compounds were retrieved, ZINC083241427, ZINC063648749, and ZINC063648753 were selected due to the binding energy they exhibited. Cheminformatics analysis revealed that the compounds possess high membrane permeability, however, BHPTP had a low membrane permeability. Furthermore, the compounds are drug like, having obeyed Lipinski’s rule of five. Conclusion: Taken together, findings from this study put ZINC083241427, ZINC063648749, and ZINC063648753 as potential ZUFSP inhibitor, however, more experimental validation is required to unravel the mechanism of actions of these compounds.
Keywords: pharmacophore modeling